The Effect of Product Knowledge, Price, and Social Media Marketing towards Consumer Buying Decision on Fit Cookie Business - Candra, Alexander Handriyan; Christiani, Natalia (P3KM Politeknik Pertanian Negeri Samarinda, 2023)
Due to Covid-19, a lot of peoples’ diet ways have changed and most of these changes are not healthy for their health. People try to consume healthy food which cannot be categorized as healthy food, especially when they want to snack. Based on this situation, a lot of food and beverage businesses have somewhat developed some kind of healthy menu to offer to consumers, which then Fit Cookie emerged and offers variant of healthy snacks and food for consumer. The purpose of this research is to find out whether product knowledge, price, and social media marketing have significant impacts towards consumer buying decisions on Fit Cookie business. The research uses a quantitative method and the survey uses the means of a questionnaire. The questionnaire assists the researcher in collecting data. It is spread to 81 people where the population and sample are the same. They are the customers of Fit Cookie. They are taken and counted from the Fit Cookie Instagram that are still becoming active buyers since the first Fit Cookie published until this research is conducted. The results show that product knowledge, price, and social media marketing has a significant and positive impact towards consumer buying decisions on Fit Cookie business.